2018
DOI: 10.1101/gad.309062.117
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 controls tumor metabolism and metastasis by regulating PGC-1α

Abstract: Mutant forms of p53 protein often possess protumorigenic functions, conferring increased survival and migration to tumor cells via their "gain-of-function" activity. Whether and how a common polymorphism in at amino acid 72 (Pro72Arg; referred to here as P72 and R72) impacts this gain of function has not been determined. We show that mutant p53 enhances migration and metastasis of tumors through the ability to bind and regulate PGC-1α and that this regulation is markedly impacted by the codon 72 polymorphism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 46 publications
8
78
0
Order By: Relevance
“…Studies show that PGC-1α uses a network of transcriptional regulators that alter metabolic function, including oxidative phosphorylation. Basu et al (2018) present evidence that mutant p53 directly binds with PGC-1α and that mutant p53 proteins with R72 bind PGC-1α less well (Fig. 1).…”
mentioning
confidence: 60%
See 2 more Smart Citations
“…Studies show that PGC-1α uses a network of transcriptional regulators that alter metabolic function, including oxidative phosphorylation. Basu et al (2018) present evidence that mutant p53 directly binds with PGC-1α and that mutant p53 proteins with R72 bind PGC-1α less well (Fig. 1).…”
mentioning
confidence: 60%
“…More importantly, is disruption of mutant p53 interactions with PGC-1α sufficient to decrease invasion and metastasis in patient tumors and improve outcome? In closing, Basu et al (2018) show evidence that R72 enhances mutant p53 interactions with PGC-1α to worsen tumor outcome. Further understanding of the influence of SNPs within the p53 pathway could facilitate the understanding of tumor progression and potentially provide new insight into the development of prognostic and therapeutic cancer modalities.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, in contrast to the wild type p53 role, mutant p53 enhances ROS level by regulating another key component of gene transcriptional machinery, i.e., PGC-1α, which is a versatile transcriptional coactivator that promotes the expression of many antioxidant/detoxifying enzymes and leads mitochondrial biogenesis [136]. In this regard, it has been demonstrated that mutant forms of p53 can inhibit PGC-1α function [137]. Furthermore, we showed that the inhibition of PGC-1α by mutant p53 is linked to the downregulation of mitochondrial UCP2 expression, favoring a determining ROS increase [8].…”
Section: Regulation Of Ros-related Transcription Factors By Mutant P5mentioning
confidence: 99%
“…These studies support the existence of different mechanisms induced by mutant p53 proteins to modulate the expression of secreted inflammatory cytokines in order to sustain an inflammatory tumor microenvironment, thus potentially contributing to promote oxidative stress and increased cancer aggressiveness. [110,117,118,120,121] R175H, R248W, R273H NF-kB Lung, pancreatic, breast and colon cancer [158][159][160][161][162] R175H, R281G, R273H Cytokines Lung, breast, pancreatic and colon cancer [157,164,165] R175H, R273H PGC1-α Lung, colon and pancreatic cancer [8,137] R175H, R280K, R273H NRF2 Colon carcinoma, oesophageal adenocarcinoma, lung and breast cancer [133][134][135] R175H, R273H AMPK Pancreatic and breast cancer [8,89,110] R175H, R248H, R273H SESNs Breast and pancreatic cancer [8,89] R175H, R273H UCP2 Lung, pancreatic and breast cancer [8] R175H, R273H GSH Oesophageal adenocarcinoma, pancreatic and breast cancer [128,135] R175H, R273H Autophagy Lung carcinoma, pancreatic and breast cancer [89]…”
Section: Stimulation Of Pro-inflammatory Cytokinesmentioning
confidence: 99%